Microgrid-Based Small Modular Reactor for a High-Renewable-Energy Penetration Grid in Ghana - Genesis Lord Asiamah; Choong-koo Chang (Energies, 2024)
Achieving the necessary energy balance entails the capacity to adapt both power supply and demand, which is known as flexible operation. At present, the Ghana National Commission on Culture depends on a combination of well-coordinated measures designed to uphold the system’s integrity when confronted with abnormal system conditions stemming from significant disturbances within the system. The set of coordinated measures comprises manual (controlled load shedding) and automatic (Special Protection Schemes, Under-Frequency Load Shedding, Over-Frequency Control Scheme, scheme against voltage collapse, etc.) steps to control important system parameters to keep the power system stable and cascading effects leading to major blackouts. Ghana’s system suffers from voltage and frequency degradation as a result of a mismatch of power supply and demand; to maintain grid stability and avoid power outages, a flexible operation is required for real-time supply and demand balancing. SMRs, with their load-following capability, can adjust their output to match the change in demand. This research proposes a microgrid-based design for a high-renewable-energy penetration grid in Ghana with the inclusion of an SMR for voltage stability.